The Role of Chemistry Learning Multimedia in Enhancing Students' Cognitive Abilities and Learning Interest - Ayu Windy Malisa Menno; A. K. Prodjosantoso (Journal of Innovation in Educational and Cultural Research, 2025)
Chemistry learning faces challenges related to students' cognitive abilities and interest in learning. One approach to address these issues is the use of multimedia in education. This study aims to analyze the role of multimedia in enhancing students' cognitive abilities and interest in learning chemistry through a systematic literature review. The review followed three stages: planning, conducting, and reporting. Data was collected from Scopus, Google Scholar, and ERIC databases, yielding 20 articles for analysis. The findings were categorized into three themes: the role of multimedia in enhancing cognitive abilities, its impact on student interest, and its integration into chemistry education. The results indicate multimedia can significantly enhance students' cognitive skills and interest in chemistry. Furthermore, various teaching approaches, such as problem-based learning, game-based learning, inquiry-based learning, cooperative TPS, and flipped classrooms, can optimize the effectiveness of multimedia in chemistry learning. This study contributes to understanding how multimedia can enhance chemistry education.